ADAPTABILITY OF THE ACCOUNTANT PROFESSION: MENGGALI MAKNAKEBERADAAN PROFESI AKUNTAN DALAM MENAVIGASI TANTANGAN DAN MEMPERTAHANKAN RELEVANSI DI ERA TRANSFORMASI DIGITAL - Eka Putra, Moh. Rizqy; Sukma Wati, Nur; Husain, Saddan; Rismala (Jurnal Bisnis dan Kewirausahaan, 2024)
This research aims to analyze the roles and functions of accountants and auditors in the context of the digital transformation era, including the challenges and opportunities they face. The research method employed is qualitative descriptive. The findings indicate that the role of the accounting profession in addressing challenges and leveraging opportunities in the digital transformation era is crucial. Accountants not only serve as conventional "bean-counters" but also as business partners providing interpretation and recommendations for strategic decision-making. Despite technological advancements such as automation and artificial intelligence posing threats to traditional accountant roles, they also present new opportunities for expanding roles as analysts and strategic advisors. To remain relevant and make significant contributions in the digital transformation era, accountants need to develop a strategic approach encompassing holistic business understanding, mastery of technological implementation, and the ability to generate greater strategic value. By adopting these strategies, accountants can sustain the relevance of their profession and make significant contributions in the digital transformation era